2008
DOI: 10.1159/000151762
|View full text |Cite
|
Sign up to set email alerts
|

Monopitched Expression of Emotions in Different Vowels

Abstract: Fundamental frequency (F₀) and intensity are known to be important variables in the communication of emotions in speech. In singing, however, pitch is predetermined and yet the voice should convey emotions. Hence, other vocal parameters are needed to express emotions. This study investigated the role of voice source characteristics and formant frequencies in the communication of emotions in monopitched vowel samples [a:], [i:] and [u:]. Student actors (5 males, 8 females) produced the emotional samples simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Consequently, differences between emotions may occur only on higher threshold levels, i.e., later in the expression. Glottal behavior has likewise been reported to affect valence perception by Laukkanen et al (1997) and (Waaramaa et al, 2008, 2010). ) Thus, from the communicative perspective, expression of valence seems to precede the expression of gender or the actual emotion in speech samples.…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, differences between emotions may occur only on higher threshold levels, i.e., later in the expression. Glottal behavior has likewise been reported to affect valence perception by Laukkanen et al (1997) and (Waaramaa et al, 2008, 2010). ) Thus, from the communicative perspective, expression of valence seems to precede the expression of gender or the actual emotion in speech samples.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, it is rather linear and, accordingly, easier to characterize and distinguish in acoustic terms. 6 Another explanation for this clear recognition offered by authors, such as Waaramaa et al, 5 is based on the fact that ''humans have had to be aware of a possible threat and be sensitively attuned to negative signals especially.'' Similarly, joy, which is also a basic emotion, though with a high level of activity, is easier to perceive than calmness and anxiety, particularly because, as Aubergé and Cathiard 28 have proven, amusement is greatly audible (84%) compared with nonamusing stimuli.…”
Section: Emma Roderomentioning
confidence: 99%
“…Conversely, sadness and desire tend overall to be formed at the lower end. 5,16,17 In this respect, the results of Mozziconacci's 2 research are interesting. It shows that joy obtained a suitable percentage of identification for the sample of 62%, whereas for sadness, the result was 97%.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that the order of emotions from smallest to largest NAQ value was anger, neutral, joy, sadness, and tenderness, meaning that anger has the most pressed voice, and tenderness the most breathy voice. However, the difficulties and effort involved in the reliable extraction of glottal flow signals by inverse filtering so far limited its application to short vowel segments (Airas and Alku, 2006;Waaramaa et al, 2008;Patel et al, 2011). Besides glottal flow parameters, also the averaged spectral energy distribution of utterances was found to differ significantly across emotions (Banse and Scherer, 1996;Johnstone and Scherer, 1999), but its relation to PT and the underlying production mechanisms has not been clarified in detail.…”
Section: Introductionmentioning
confidence: 99%